Effect of Ascorbic Acid Concentration on the Stability of Tartrate-Capped Silver Nanoparticles - Indah Miftakhul Janah; Roto Roto; Dwi Siswanta (Universitas Gadjah Mada, 2022)
In this work, tartrate-capped silver nanoparticles (AgNPs) by reducing Ag+ ions into Ag0 using L-ascorbic acid and capping disodium tartrate have been prepared. The reaction was carried out at room temperature in an alkaline medium of pH 11 to obtain a rapid and one-step green synthesis method. The effect of L-ascorbic acid concentration on the synthesis preparation was studied to investigate their impact on the particle size, morphology, and stability of the AgNPs. The obtained tartrate capped AgNPs have SPR absorbance in 390–410 nm. They have a spherical shape, as confirmed by TEM. Increasing L-ascorbic acid concentrations from 25 mM to 100 and 200 mM leads to the 27, 17, and 11 nm particle size distributions. They give the zeta potential of –33.5, –20.8, and –21.3, respectively. After a week, the decreasing absorbance peaks were 0.151, 0.0105, and 0.336 a.u. The optimum L-ascorbic acid concentration was obtained at 100 mM, indicated by the smallest FWHM point. Thus, we may conclude that lower or higher levels of reducing agents resulted in low stability. Therefore, controlling L-ascorbic acid concentration is an important parameter. A sufficient concentration and an appropriate capping agent can produce good nanoparticle stability essential for further application.